2009
DOI: 10.1590/s0100-204x2009001100017
|View full text |Cite
|
Sign up to set email alerts
|

Expressão dos genes nodC, nodW e nopP em Bradyrhizobium japonicum estirpe CPAC 15 avaliada por RT-qPCR

Abstract: Resumo -O objetivo deste trabalho foi avaliar a expressão, por RT-qPCR, dos genes de nodulação nodC e nodW e do gene nopP da estirpe CPAC 15, que provavelmente atuam na infecção das raízes da soja. Foram realizados dois experimentos. No primeiro, a expressão dos genes foi avaliada nas células após a incubação com genisteína por 15 min, 1, 4 e 8 horas. Os resultados revelaram que os três genes apresentaram maior expressão imediatamente após o contato com o indutor (15 min). No segundo experimento, a bactéria fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
4
0
6
Order By: Relevance
“…Several studies have previously observed late gene expression in bacterial isolates, such as studies with nodC and nodW nodulation genes and the nopP gene in Bradyrhizobium japonicum, which probably act on the infection of soybean roots (Bortolan, Barcellos, Marcelino, & Hungria, 2009), or expression of GDH gene in Lactobacillus plantarum DPPMA49 in response to different environmental conditions (De Angelis et al, 2010), which revealed differences in the activation of the gene expression machinery in response to the medium.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have previously observed late gene expression in bacterial isolates, such as studies with nodC and nodW nodulation genes and the nopP gene in Bradyrhizobium japonicum, which probably act on the infection of soybean roots (Bortolan, Barcellos, Marcelino, & Hungria, 2009), or expression of GDH gene in Lactobacillus plantarum DPPMA49 in response to different environmental conditions (De Angelis et al, 2010), which revealed differences in the activation of the gene expression machinery in response to the medium.…”
Section: Resultsmentioning
confidence: 99%
“…Varios estudios han demostrado que estas proteínas pueden promover o prevenir la nodulación dependiendo de la planta hospedadora Schechter et al, 2010). Las proteínas de nodulación externas (NOP) son al menos 20 proteínas que atraviesan la membrana de la célula vegetal a través del sistema de transporte SSTT, y actúan en el citoplasma alterando su metabolismo o causando la supresión de la defensa del hospedante contra los microorganismos (Bortolan et al, 2009). El gen nopP ha sido encontrado en unas pocas especies de rizobios (Rhizobium sp.…”
Section: Discussionunclassified
“…NGR234, Sinorhizobium fredii, y B. japonicum) y está ausente en bacterias patogénicas . Si bien la función de esta y otras proteínas Nop durante la nodulación aún no han sido caracterizadas (Schechter et al, 2010), se ha sugerido que este gen actúa suprimiendo las defensas del huésped mediante la inhibición de la respuesta hipersensible, lo que indirectamente contribuye al desarrollo de un mayor número de infecciones (Lang et al, 2008;Saad et al, 2005;Bortolan et al, 2009). Varios trabajos sugieren que el estudio de la funcionalidad de este gen de B. japonicum pueden ser clave para conocer más profundamente los mecanismos de competitividad y eficiencia en la fijación de N 2 .…”
Section: Discussionunclassified
See 2 more Smart Citations